Adaptive double auction mechanism for cloud resource allocation - Ding DING; Si-wei LUO; Li-hua AI (Tongxin xuebao)
By integrating the auction mechanism in economic field into cloud,an adaptive double auction mechanism(ADAM) was proposed to allocate resources in cloud computing.Compared to traditional double auction mechanisms,ADAM traded cloud resource sellers and cloud resource buyers at their expected price and quantity,guaranteed the profits of all participants.Moreover,ADAM applied different auction rules in different cases to satisfy as more participants as possible.As a new mechanism for cloud resource allocation,ADAM was proved to be strategy-proof,weakly budget-balanced and individual rational even under the conditions that the price and quantity of participants were private information.Simulation results also confirm that ADAM outperforms the traditional one on both cloud user satisfaction degree and cloud resource utilization rate and is also economically efficient,especially as more users are involved in the auction market.